EFL STUDENTS’ PERCEPTION OF USING KAHOOT APPLICATION IN VOCABULARY LEARNING: THE CASE OF SECONDARY SCHOOL IN INDONESIA - Napitupulu, Thea Clarissa Napitupulu (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2023)
This study aims to perceive EFL students’ perception in learning vocabulary through kahoot application. This research focuses on the context of secondary schools in Indonesia. The study employes a qualitative descriptive method as a case study. The researcher chooses case study because a case study is a research to identify an issue or a problem. 14 secondary students in the tenth grade were rectruited in the study. The instrument of this research is questionnaire which questions about students’ perception in vocabulary learning with Kahoot . Another tool used to collect data in this study is interview. The data gathered from the questionnaire and interview is condensed by summarizing and choosing key topics. Thematic content analysis was used to analyse the interview data. Students' perceptions of Kahoot are very positive because it helps them develop themselves. The result of interview shows that all students indicated that they had a positive perception of Kahoot. All students agree if Kahoot is very useful in learning to know new vocabulary, meaningful interaction, and engagement. This research shows that students' perceptions of Kahoot's application is positive to improve vocabulary learning. The overwhelmingly positive response from students, along with their opinions on Kahoot increased enthusiasm, effective vocabulary acquisition, and a lively classroom atmosphere.